(untitled) (International Journal of Engineering and Computer Science, 2023)
Customer satisfaction has become the primary target for each successful running business currently. They have the true potential in uplifting a tiny business overnight to completely shutting down a brand. Real time analysis of customer opinion (sentiment) is the backbone of this success. Thus this piece of research tries to focus light on the challenges encountered by businesses in four categories of opinion mining. Natural Language Processing with machine learning algorithms works wonders for opinion mining. What is important is the correct choice of opinion mining for a specific type of business as each one of them demands an idiosyncratic approach. The research indeed shares a quick infusion for businesses to safeguard. Countless advice is beared by businesses to have real time analysis, but this research endeavor by showcasing its ideal infusion.